Cloud computing in E-Commerce in Palestine: legal issues and challenges - Hasan, Yahya Y. F.; Zulhuda, Sonny (Zesdyzar Rokman Resources, 2015)
Today’s infrastructure of e-commerce increasingly depends on cloud computing. Companies use cloud computing in ecommerce, because it prevents data loss and provides a complete network with hardware and software, which further enables the merchant to manage their e-transaction in the best possible manner. On the other hand, cloud computing provider is obliged to provide the merchant with the best solution based on their respective agreements. In addition, providing adequate levels of security while using the cloud computing service is equally important because any breach of security will affect the reputation of the merchant and provider, and affect the users via loss or leakage of their data. Although the benefits of cloud computing to the merchants and consumers in e-transaction are clear, there are undoubtedly some challenges and concerns. This paper will discuss these challenges of using cloud computing within e-commerce including the liability surrounding the data security and privacy in the cloud. In addition, this paper seeks to clarify the provider’s liability for loss or destruction of the information during cloud computing. Furthermore, this study aims to examine the legality of unfair contract terms in the cloud computing contracts under the Palestinian laws. This study mainly used the analytical and library research to examine the main issues of cloud computing. The laws of Palestine and the Directive 95/46/EC are used in this study to clarify the legal positions on the relevant issues above. It is found from this study that the current laws in Palestine are inadequate to regulate the cloud computing issues. The outlying contract should include a high level of security to the customer to protect their data and information in cases of cloud computing. The cloud provider should provide the appropriate technical means and the procedures to protect personal data against any accident of loss, unauthorized disclosure, and access or transfer of the data via the Internet. The benefit of this paper is to propose some recommendations to develop the Palestinian laws in order to address the issues of cloud computing which will contribute in the development of e-commerce in Palestine.